To solve this system of equations, we will first substitute the second equation into the first equation to eliminate x.
Plugging x=5y-1 into the first equation:
2(5y-1) + 6y = -18
10y - 2 + 6y = -18
16y - 2 = -18
16y = -16
y = -1
Now that we have found the value of y, we can substitute it back into the second equation to find the value of x.
x = 5(-1) - 1
x = -5 - 1
x = -6
Therefore, the solution to the system of equations is x = -6 and y = -1.
Solve the system of equations.%0D%0A2x+6y=−18 %0D%0Ax=5y−1
1 answer